Changes in the Number of Symbionts and Symbiodinium Cell Pigmentation Modulate Differentially Coral Light Absorption and Photosynthetic Performance - Scheufen, Tim; Iglesias-Prieto, Roberto; Enríquez, Susana (Frontiers in Marine Science, 2017)
In order to understand the contribution of pigmented coral tissues to the extraordinary optical properties of the coral-symbiont-skeleton unit, we analyzed the associations between structural and optical traits for four coral species, which broadly differ in skeleton morphology, tissue thickness and in the variation of coral pigmentation, symbiont content, Symbiodinium dominant type and Symbiodinium cell pigmentation (Ci). Significant differences among species were found for the maximum capacity of light absorption (Amax) and for the minimum pigmentation required to reach that maximum. The meandroid morphotype represented by Pseudodiploria strigosa showed a slightly lower Amax than the other three chalice-type species, while the thickest species, Montastraea cavernosa, required 2 to 3.5 times higher pigmentation to reach Amax. In contrast, Orbicella faveolata and O. annularis, which were able to harbour high number of symbionts and achieve the highest photosynthetic rates per area, showed the largest abilities for light collection at decreasing symbiont densities, leading to a more fragile photophysiological condition under light and heat-stress. Holobiont photosynthesis was more dependent on Symbiodinium performance in the less populated organisms. At reduced pigmentation, we observed a similar non-linear increase in holobiont light absorption efficiency (a*Chla), which was differentially modulated by reductions in the number of symbionts and Symbiodinium Ci. For similar pigmentation, larger symbiont losses relative to Ci declines resulted in smaller increases in a*Chla. Two additional optical traits were used to characterize light absorption efficiency of Symbiodinium (a*sym) and coral host (a*M). Optimization of a*sym was well represented by P. strigosa, whereas a*M was better optimized by O. annularis. The species with the largest symbiont content, O. faveolata, and with the thickest tissues, M. cavernosa, represented, respectively, less efficient solutions for both coral traits. Our comparison demonstrates the utility of optical traits to characterize inter-specific differences in coral acclimatization and performance. Furthermore, holobiont light absorption efficiency (a*Chla) appeared as a better proxy for the “bleached phenotype” than simple reductions in coral color. The analysis of a putative coordinated variation in the number of symbionts and in Symbiodinium cell pigmentation deserves special attention to understand holobiont optimization of energy collection (a*Chla) and photosynthetic performance.